2011
DOI: 10.1902/jop.2011.110103
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Phosphate/Pyrophosphate Metabolism to Regenerate the Periodontium: A Novel In Vivo Approach

Abstract: Background The developing periodontium is sensitive to local levels of phosphate (Pi) and pyrophosphate (PPi), as demonstrated by cementum phenotypes resulting from loss of function of protein regulators of Pi/PPi homeostasis. The progressive ankylosis protein (ANK) regulates transport of PPi, and Ank knock-out (KO) mice feature rapidly forming and thick cementum. We hypothesized that, besides affecting cementum formation, decreased extracellular PPi levels in Ank KO mice would also impact cementum regeneratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 37 publications
5
34
0
Order By: Relevance
“…47 The results from these regeneration studies support our findings here. Specifically, we demonstrated that cementum regeneration in Ank KO mice (which feature PP i deficiency) was more rapid and more extensive when compared to comparably treated control mice.…”
Section: Discussionsupporting
confidence: 89%
“…47 The results from these regeneration studies support our findings here. Specifically, we demonstrated that cementum regeneration in Ank KO mice (which feature PP i deficiency) was more rapid and more extensive when compared to comparably treated control mice.…”
Section: Discussionsupporting
confidence: 89%
“…37 Recently, signalling cascades connecting dentin matrix protein 1 and dentin sialophosphoprotein were studied in rodent models. 35 Similar models with sclerostin might confirm the recent findings, as Wnt/β-catenin signalling is complex. 2 Moreover, mouse models revealing the role of DKK-1, another antagonist of Wnt/β-catenin signalling, on the tooth, the dimension of the tooth and the periodontium would be worth investigating, particularly because DKK1 is a negative regulator of normal bone homeostasis in vivo .…”
Section: Discussionsupporting
confidence: 76%
“…22 This supports the role of Wnt/β-catenin signalling in the formation of the dentoalveolar complex. 31 Whether sclerostin is functionally linked with the control of acellular cementum in phosphate metabolism 32,33 and mutations of the progressive ankylosis protein and plasma cell membrane glycoprotein-1 genes 34,35 remains unclear. However, mouse models provide valuable insights into the biology of the mysterious process of cementogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Inorganic pyrophosphate (PPi) is present in mineralized tissues and is a potent inhibitor of HAp crystal growth. Increases in Pi concentration will facilitate HAp formation, which is highly sensitive to the balance of Pi/PPi [Cheng and Pritzker, 1983;Rodrigues et al, 2011].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, Zn 2+ can compete with Ca 2+ for binding to pyrophosphate, even at a very low concentration, resulting in the enhanced formation of HAp [Vasant and Joshi, 2011]. Moreover, the non-specific-tissue alkaline phosphatase that is present in dentin [Rodrigues et al, 2011] and is specifically activated by zinc [Seo et al, 2010;Yamaguchi, 2010] can also hydrolyze pyrophosphates. These two factors probably work in concert to control local levels of pyrophosphates favoring dentin remineralization.…”
Section: Discussionmentioning
confidence: 99%